AN ANALYSIS OF THE JARGON EXPRESSIONS IN THE CRUISE LINE - Sumertha, Putu Adi; Suputra, Putu Eka Dambayana; Suprianti, G A.P (Universitas Pendidikan Ganesha, 2021)
ABSTRACTThe jargon used by the crews in housekeeping and food and beverage service department in the cruise line was analyzed in this research. The jargon expressions in these departments have special meaning that confused the other people outside the group. The jargon used in this department. This research used descriptive qualitative research with the basic interpretative studies to understand the meaning of every jargons in the cruise line crews related to the crews working experiences interacted with the guest around them. The open questionnaire and the interview guide were used to collect the data from 4 subjects of the study workingÂ experiences in the cruise line. From two subjects that worked in the housekeeping department, there were 116 jargons expressions that were classified into four jargon forms. There were 24 jargons in a word form, 37 jargons in phrase form, 40 jargons in abbreviation form (initialism type), 10 jargons in abbreviation form (shortening type), and 5 jargons in acronym form. From two subjects that worked in the food and beverage service department there were 136 jargons expressions that were classified into four jargon forms. There were 27 jargons in word form, 77 jargons in phrase form, 19 jargons in abbreviation form (initialism type), 8 jargons in abbreviation form (shortening type), and 4 jargons in acronym form. Every meaning of the jargon expressions were suitable with the department condition and situation. There are four functions of jargon expressions. Those are able to provide a clear and unambiguous term, promoting their group solidarity and exclude as out-groupers, marking the group membership, and representing the product. This research can be used as a reference to know the jargon used in the cruise line hotel operational division.